Simulação de cenários de sustentabilidade hídrica da orizicultura na sub-bacia hidrográfica do Arroio Grande através da implantação de barragens temporárias - Salbego, Adriana Gindri (2010)
Water shortages in certain periods have led to serious social conflicts, as well as economic and environmental impacts resulting from irrigated agriculture, especially of rice growing, which represents a high demand of water. The present study proposes a methodology for analyzing the water sustainability of rice growing through the implementation the temporary dams at the river-bed of water courses, with the study area the watershed of Arroio Grande, which has a growing need to match the conditions of supply and demand. The analysis of water supply and demand conditions was made in the context of the watershed and by control point, three scenarios are composed: scenarios 1 - the existing situation; scenario 2: considers compliance to environmental legislation, with elimination of rice growing areas in areas of permanent preservation and destination of the portion of environmental flow (30%Q90) an; scenario 3: considers compliance to environmental legislation and implementation the temporary dam at the river-beds of water courses upstream of where the shortage was indicated, as a way to expand and ensure water supply for rice growing. The results show that the in the scenario 1 the demand is met, although for control points 5 and 6 it is equivalent to 89% to 97% of its availability, besides not meet environmental legislation. For the scenario 2, control points 5 and 6 indicate water scarcity for the months analyzed (November February), indicating the places where water supply should be expanded. In scenario 3, it is concluded that the temporary dams proposed have the may partially meet the water requirements and PC 5, PC 6, the results indicate no compliance between supply and demand. Therefore, concluded that the conflicts over water use in the watershed of the Arroio Grande resulting from irrigated agriculture can be minimized with the installation of temporary dams. However, the results indicate that the water sustainability of rice growing can only be achieved by reducing the irrigated area, specifically between the PC 3-5 and 4-6.